Identifikasi Partisipatif Sumber Pendapatan Asli Desa Berkelanjutan: Pengabdian Masyarakat di Desa Batu Tering - Sudrajat Martadinata; Tri Satriawansyah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Participatory identification activities for sustainable Village Original Income sources in Batu Tering Village have successfully identified local potentials that are relevant to the principles of sustainability, such as the development of ecotourism and local products, which have the potential to increase village income. This participatory approach increases community awareness and participation in the management of village resources, as well as strengthening the governance of Village-Owned Enterprises that are more transparent and accountable. Thus, this activity not only has the potential to increase Village-Owned Enterprises, but also to create a conducive ecosystem for sustainable and inclusive village development, where the community has a sense of ownership and responsibility for the progress of their village. Increasing community awareness and knowledge about the importance of BUMDes must continue to be carried out, involving various stakeholders